Grassland soil tillage by three implements in an Ultisol and its physical and hydropedological implications - Camacho, Manuel E. (2015)
A field study was conducted to test the effects of soil tillage with 3 different implements on compaction, physical and hydropedological properties of an Ultisol under cattle production, located in San Mateo, Alajuela. An area of approximately 10 000 m2 was selected and divided into 16 plots (650 m2 each) and was tilled with 3 different implements corresponding to the treatments, following an unrestricted random experimental design, with a plot as experimental unit. Soil without tillage (T), tillage by spader plow (PM), tillage by chisel plow (C) or tillage by subsoiler (S) were established as treatments. Forty days after tillage treatments, soil penetration resistance every 5 cm up to 50 cm deep was assessed, and gravimetric moisture content, bulk and particle density, water infiltration and hydraulic conductivity, all of them up to the first 10 cm deep, all of them were measured. Soil compaction, expressed as soil penetration resistance, was reduced by tillage treatments; the lowest values for soil compaction were found in the spader plow treatment (PM). This same treatment enhanced cumulated infiltration (38.70±3.60 mm at 150 min) significantly, comparing with those obtained in T treatment (0.09±0.02 mm at 150 min). No significant differences were found among tillage treatments for bulk density, total porosity and airspace, but comparing with control treatment (T) they were found. Subsoiler treatment (S) favored the highest values for hydraulic conductivity, but no significant differences with the other treatments were found (p>0.05).